Educational Barriers for Children? A Study of Fulfillment to the Rights of Education for Undocumented Indonesian Children in Malaysia - Markus Andre Mefiboset Simbolon (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
Indonesia and Malaysia, as neighboring countries, share deep historical, economic, and social ties, leading to significant migration flows between them. However, alongside legal migration, a considerable number of undocumented Indonesian migrants reside in Malaysia, often accompanied by their children, who are born without proper documentation. These undocumented children face severe barriers to education, as Malaysia’s legal framework, influenced by its reservation to Article 28 of the CRC, restricts access based on nationality and legal status. Despite both states being parties to the CRC, which mandates equal educational rights for all children without discrimination, Malaysia’s policies continue to exclude undocumented children from formal education. This study examines Malaysia’s legal stance, its contradiction with CRC obligations, and the impact on Indonesian children. Malaysia, as the host state, must take greater responsibility by ensuring non-discriminatory access to education and aligning its legal framework with its international commitments. The withdrawal of Malaysia’s reservation to Article 28 CRC and potential constitutional amendments are necessary steps toward fulfilling the right to education for all children within its territory.